Reyes Escate, Luis Fernando de Jesús. Negros derives: following the trajectories of material negritudes in Bolivia. Porto Alegre: Editora da UFRGS, 2018. 184 pp. - Silva, Marcos Antonio Batista da (2020)
The objective of this review is, starting from the learning and experience process with the Tocañeros, to analyze the processes of black identity constitution among the inhabitants of the Afro-Bolivian Community of Tocaña. The work demands of the reader a set of reflections generated from the black bodies and the flows of blackness, crossed by the paths traveled and narrated by the author.